Malaria in Brazil : an overview - Ferreira, Joseli Oliveira (2010)
Malaria is still a major public health problem in Brazil, with approximately 306 000 registered cases in 2009, but it is estimated that in the early 1940s, around six million cases of malaria occurred each year. As a result of the fight against the disease, the number of malaria cases decreased over the years and the smallest numbers of cases to-date were recorded in the 1960s. From the mid-1960s onwards, Brazil underwent a rapid and disorganized settlement process in the Amazon and this migratory movement led to a progressive increase in the number of reported cases. Although the main mosquito vector (Anopheles darlingi) is present in about 80% of the country, currently the incidence of malaria in Brazil is almost exclusively (99,8% of the cases) restricted to the region of the Amazon Basin, where a number of combined factors favors disease transmission and impair the use of standard control procedures. Plasmodium vivax accounts for 83,7% of registered cases, while Plasmodium falciparum is responsible for 16,3% and Plasmodium malariae is seldom observed. Although vivax malaria is thought to cause little mortality, compared to falciparum malaria, it accounts for much of the morbidity and for huge burdens on the prosperity of endemic communities. However, in the last few years a pattern of unusual clinical complications with fatal cases associated with P. vivax have been reported in Brazil and this is a matter of concern for Brazilian malariologists. In addition, the emergence of P. vivax strains resistant to chloroquine in some reports needs to be further investigated. In contrast, asymptomatic infection by P. falciparum and P. vivax has been detected in epidemiological studies in the states of Rondonia and Amazonas, indicating probably a pattern of clinical immunity in both autochthonous and migrant populations. Seropidemiological studies investigating the type of immune responses elicited in naturally-exposed populations to several malaria vaccine candidates in Brazilian populations have also been providing important information on whether immune responses specific to these antigens are generated in natural infections and their immunogenic potential as vaccine candidates. The present difficulties in reducing economic and social risk factors that determine the incidence of malaria in the Amazon Region render impracticable its elimination in the region. As a result, a malaria-integrated control effort - as a joint action on the part of the government and the population - directed towards the elimination or reduction of the risks of death or illness, is the direction adopted by the Brazilian government in the fight against the disease.